3D Interconnected Electrode Materials with Ultrahigh Areal Sulfur Loading for Li–S Batteries. Issue 17 (2nd March 2016) - Fang, Ruopian; Zhao, Shiyong; Hou, Pengxiang; Cheng, Min; Wang, Shaogang; Cheng, Hui‐Ming; Liu, Chang; Li, Feng
Abstract : Sulfur electrodes based on a 3D integrated hollow carbon fiber foam (HCFF) are synthesized with high sulfur loadings of 6.2–21.2 mg cm −2 . Benefiting from the high electrolyte absorbability of the HCFF and the multiple conductive channels, the obtained electrode demonstrates excellent cycling stability and a high areal capacity of 23.32 mAh cm −2, showing great promise in commercially viable Li–S batteries.